Nemaline myopathy with scoliosis: a case report - Huang, Jin; Zhang, Chen; Li, Jing; Wang, Huaming; Cui, Xiaojuan; Wang, Juan; Zhang, Borong; Wang, Xiaoqiang; Lin, Deming; Zhao, Jun; Wen, Jiantao (Frontiers in Pediatrics, 2024)
Nemaline myopathy (NM) is a rare congenital muscle disease that leads to muscle damage, resulting in muscle weakness and atrophy. Cases of scoliosis induced by muscle weakness and atrophy are exceedingly uncommon. The author clinically treated one patient with NM complicated by scoliosis and analyzed its clinical characteristics through a literature review. The pathogenic genes of this patient originated from compound heterozygous mutations c.12471 + 3A>G from the mother and c.7727G>A from the father, leading to the diagnosis of NM accompanied by scoliosis, which represents a relatively rare clinical phenotype.